Estudo fitoquímico de Eugenia myrcianthes: busca de substâncias bioativas - Batalhão, Jaqueline Raquel (2014)
The search for new substances with bioactive potential is the target of numerous studies inserted in the chemistry of natural products, since it involves the isolation, the structural elucidation, as well as the action mechanism of the compounds. Some species of Eugenia were widely studied showing a great diversity of secondary metabolites associated with different biological activities of their constituents, which have justified the interest in the study of species of this family in the search for active compounds. The Eugenia myrcianthes specie has its chemical and biological potential little known. In this context, the aim of this study was the phytochemistry study of E. myrcianthes seeking isolation and characterization of their chemical constituents, as well as evaluation of the effect of crude extracts, fractions and isolated substances, performing antifungal, antimicrobial, antioxidant and insecticidal assays. This study allowed the isolation and/or identification of eight flavonoid glycosides: myricetin-3-O-α-L-rhamnoside (Myricetrin), myricetin-3-O-α-L-arabnopyranoside, myricetin-3-O-α-L-arabnofuranoside, myricetin-3-O-β-D-glucopyranoside, myricetin-3-O-β-D-glalactopyranoside, quercetin-3-O-α-L- arabnopyranoside (Guajavarin), quercetin-3-O-α-L-arabnofuranoside (Avicularin) and quercetin-3-O-β-L-xyloside, one coumarin: xanthyletin, two triterpenes: 3β-O-cis-p-coumaroil-α-amyrin and 3β-O-trans-p-coumaroil-α-amyrin, one tyrosol derivative: 2-(4'-hydroxyphenyl)ethyl tricosanoate, one alcohol of long chain: 1-octacosanol and one sterol: β-sitosterol. The crude extracts from the leaves, twigs, and the fractions hexane, ethyl acetate and hydroalcoholic of the leaves of E. myrcianhtes and some pure substances were tested against leaf cutting ant Atta sexdens rubropilosa; its symbiotic fungus Leucoagaricus gongylophorus; for antimicrobial activity by microdilution technique, against the microorganisms Pseudomonas aeuroginosas, Bacillus subtilis, Microccocus luteus, Candida albicans and Candinda tropicalis. They were also evaluated for antioxidant activity using the technique of suppression of radical species, DPPH (2-diphenyl-1-picrylhidrazile).